Haematoietic stem cell transplantation in adult and pediatric patients - Majka, Ewelina; Samardakiewicz, Marzena (Nursing in the 21st Century, 2012)
HAEMATOIETIC STEM CELL TRANSPLANTATION IN ADULT AND PEDIATRIC PATIENTSDynamic progress of transplant medicine which took place at the turn of final years contributed up to the increased number of conducted transplants of erythrogenic cells both at children as well as adults. The optiumum number of transplant centres in Poland lets the majority for performing the surgery on the transplant of the bone marrow for patients, however above all a market is a main problem which much the possibility of conducted transplants is limiting, in the process giving the chance of healing low figure of registered donors Central Register of Unrelated Donors of the bone marrow and cord blood (on nearly 40 m inhabitants of Poland registered with Central Register of Unrelated Donors of the bone marrow and cord blood it is only c 35 tys. of volunteers). In Poland the every second person ill from leukaemia isn't finding the right donor amongst unrelated persons. Therefore is important, in order to of potential donors was like the most what will let sick persons lengthen the odds on finding it appropriate.